Features and Frequency of Complications Among Pilgrims with Diabetes During Hajj - Sanobia Yousuf; Muhammad Y Ahmedani (Journal of Diabetology)
Abstract Aim and Objective: To observe the features and frequency of complications among pilgrims with diabetes during Hajj. Materials and Methods: This retrospective observational study was conducted at the Baqai Institute of Diabetology and Endocrinology (BIDE). People with diabetes who visited the outpatient department of BIDE after Hajj were invited to participate in the study between August and September 2018 and 2019, respectively. Those who were not willing to participate or perform Hajj have been excluded. The data collection was done by using a predesigned, close-ended questionnaire, including demographic and clinical parameters, practice compliance toward management, and the frequency of complications that occurred during Hajj. Results: In this study, a total of one hundred and forty-one people with diabetes participated with a mean age of 55.41 ± 10.6 years. Out of these, 111 (78.7%) had visited their health care professionals for pre-Hajj consultation and education, 134 (95%) received their recommended vaccination, and 92 (65.2%) of the people had checked their HbA1c before going to perform Hajj. Diabetic foot problems were recorded in 27 (19.1%), and respiratory diseases were found in 18 (12.8%). A total of 38 (27%) of the study population have reported hypoglycemia, and 51 (36.4%) have reported hyperglycemia. Conclusion: In this study, a higher frequency of glycemic as well as foot complications was observed among pilgrims with diabetes. Pre-Hajj education is mandatory to prevent these avoidable problems.